Clinical characteristics and outcomes of immunocompromised patients with severe community-acquired pneumonia: A single-center retrospective cohort study - Wu, Xiaojing; Sun, Ting; Cai, Ying; Zhai, Tianshu; Liu, Yijie; Gu, Sichao; Zhou, Yun; Zhan, Qingyuan (Frontiers in Public Health, 2023)
Background: Immunocompromised patients with severe community-acquired pneumonia (SCAP) warrant special attention because they comprise a growing proportion of patients and tend to have poor clinical outcomes. The objective of this study was to compare the characteristics and outcomes of immunocompromised and immunocompetent patients with SCAP, and to investigate the risk factors for mortality in these patients. Methods: We conducted retrospective observational cohort study of patients aged ≥18 years admitted to the intensive care unit (ICU) of an academic tertiary hospital with SCAP between January 2017 and December 2019 and compared the clinical characteristics and outcomes of immunocompromised and immunocompetent patients. Results: Among the 393 patients, 119 (30.3%) were immunocompromised. Corticosteroid (51.2%) and immunosuppressive drug (23.5%) therapies were the most common causes. Compared to immunocompetent patients, immunocompromised patients had a higher frequency of polymicrobial infection (56.6% vs. 27.5%, P < 0.001), early mortality (within 7 days) (26.1% vs. 13.1%, P = 0.002), and ICU mortality (49.6% vs. 37.6%, P = 0.027). The pathogen distributions differed between immunocompromised and immunocompetent patients. Among immunocompromised patients, Pneumocystis jirovecii and cytomegalovirus were the most common pathogens. Immunocompromised status (OR: 2.043, 95% CI: 1.114–3.748, P = 0.021) was an independent risk factor for ICU mortality. Independent risk factors for ICU mortality in immunocompromised patients included age ≥ 65 years (odds ratio [OR]: 9.098, 95% confidence interval [CI]: 1.472–56.234, P = 0.018), SOFA score (OR: 1.338, 95% CI: 1.048–1.708, P = 0.019), lymphocyte count < 0.8 × 109/L (OR: 6.640, 95% CI: 1.463–30.141, P = 0.014), D-dimer level (OR: 1.160, 95% CI: 1.013–1.329, P = 0.032), FiO2 > 0.7 (OR: 10.228, 95% CI: 1.992–52.531, P = 0.005), and lactate level (OR: 4.849, 95% CI: 1.701–13.825, P = 0.003). Conclusions: Immunocompromised patients with SCAP have distinct clinical characteristics and risk factors that should be considered in their clinical evaluation and management.